1977
DOI: 10.1093/ageing/6.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Infarction Coincident With Cerebrovascular Accidents in the Elderly

Abstract: In a three-year prospective study of acute cerebrovascular accident patients admitted to a geriatric unit within 72 hours of the onset, 12.7% had what was considered to be an associated acute myocardial infarction. In the majority of cases, 71%, there was no clinical indication of an acute myocardial infarction and, had it not been for electrocardiographic and enzyme studies, the concurrence of these two conditions might not have come to light. The possible explanations for the concurrence of these two conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

1980
1980
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 0 publications
1
25
0
1
Order By: Relevance
“…In clinical studies, myocardial ischemia has been implicated as the cause of ECG changes in LV dysfunction. 12,15,16 However, substantial evidence from animal models suggests that excessive release of catecholamines from sympathetic nerve terminals in the myocardium is a more likely cause of cardiac injury after SAH. 2 The exact mechanism of catecholamine-mediated myocardial damage is unknown, although persistent activation of calcium channels, membrane damage, and microvascular spasm have been proposed as causes.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical studies, myocardial ischemia has been implicated as the cause of ECG changes in LV dysfunction. 12,15,16 However, substantial evidence from animal models suggests that excessive release of catecholamines from sympathetic nerve terminals in the myocardium is a more likely cause of cardiac injury after SAH. 2 The exact mechanism of catecholamine-mediated myocardial damage is unknown, although persistent activation of calcium channels, membrane damage, and microvascular spasm have been proposed as causes.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence over the years has subsequently reported the association between AIS and AMI. Chin et al (1) reported the incidence of CCI as 12.7% in geriatric patients who were screened for AMI within 72 hours of admission for acute stroke. Findings from the Global Registry of Acute Coronary Event (GRACE) trial reported an incidence of in-hospital stroke as 0.9% in a cohort of patients presenting with acute coronary syndrome, and the incidence was much higher in patients with STEMI than the non-STEMI (8).…”
Section: Epidemiologymentioning
confidence: 99%
“…The association between both conditions was recognized few decades ago from several studies, including a 3-year prospective study of AIS patients admitted to the geriatric unit (1). The study showed that 12.7% of these patients had associated AMI within 72 hours of admission.…”
Section: Introductionmentioning
confidence: 96%
“…Concomitant acute myocardial infarction and ischemic cerebrovascular strokes has been rarely reported in the literature [1]. In this report, after the patient has developed acute transmural infero-posterior and right ventricular infarction he suddenly developed a rapid onset and a progressive course of worsening of his conscious level with an NIHSS >25 [2] denoting severe ischemia.…”
Section: Discussionmentioning
confidence: 94%